Relationships between Functional Movement Quality and Sprint and Jump Performance in Female Youth Soccer Athletes of Team China - Junjie Zhang; Junlei Lin; Hongwen Wei; Haiyuan Liu (MDPI AG, 2022)
This study aimed to determine the optimal functional movement screen (FMS) cut score for assessing the risk of sport injury, and to investigate the correlations between functional movement quality and sprint and jump performance. Twenty-four (N = 24) athletes performed all tests in one day at 10-30 min intervals, and the FMS test was performed first, without a warm-up session. After a standard warm-up, athletes then completed the Y-balance Test (YBT), sprint, counter-movement jump (CMJ), and standing long jump (SLJ), in turn. For each test, the best of three attempts was recorded for further analysis. A receiver operating characteristic (ROC) curve and area-under-the-curve (AUC) were used to determine the optimal FMS cut score for assessing the risk of sport injuries, and Spearman's rank correlation analysis was used to quantify associations between functional movement scores and athletic performance. The average FMS score was 16.2 and the optimal FMS cut score for assessing the risk of sport injuries was 14.5. There were moderate relationships between total FMS score and 10-20 m sprint time (r = −0.46, p < 0.05), between In-line Lunge and 0-20 m sprint time (r = −0.47, p < 0.05), between Shoulder Mobility and 0-10 m sprint time (r = −0.48, p < 0.05), and between Trunk-stability Push-up and 10-20 m sprint time (r = −0.47, p < 0.05). Moreover, Hurdle Step score was largely correlated with 0-10 m time (r = −0.51, p < 0.05). For Y-balance, moderate correlations were observed between CMJ height and anterior asymmetry score (r = −0.47, p < 0.05) and posteromedial asymmetry score (r = −0.44, p < 0.05). However, there were no significant associations between YBT performance (asymmetric in three directions and composite score) and sprint performance (p > 0.05). Taken together, the results indicate that a FMS score of 14 is not a gold standard for assessing the risk of injury in all populations; we recommend that the FMS cut score of 14.5 should be the optimal score for assessing risk of injury in young female elite soccer players. Moreover, the FMS and YBT were introduced to assess the quality of functional movements, and they cannot be used to assess sprint and jump performance. Practitioners can use components of the FMS that have similar characteristics to specific sports to assess athletic performance.